Natural gas reserve/production ratio in Russia, Iran, Qatar and Turkmenistan: A political and economic perspective. (June 2016) - Esen, Vedat; Oral, Bulent
Abstract: In this study, changes in natural gas reserve/production ratio ( R / P ) of the four countries having the highest natural gas reserves (Russia, Iran, Qatar, Turkmenistan), the importance of which increases in the world market each day due to developing technology and the demand for clean energy, has been analyzed depending on the economic and political developments in national and international fields. Change of R / P ratio depending on years has been displayed on graphics from different sources and these alterations have been tried to be associated with such issues as natural gas agreements in history, handover of political authority, economic crises etc. Therefore; it has been put forward whether or not political and economic changes of the countries are factors on the amount of natural gas production and the discovery of new reserve fields with the addition aim of providing a general overview on natural gas market. Highlights: Russia, Iran, Qatar and Turkmenistan are the top four countries with the highest natural gas reserves. R / P ratios of Russia, Iran, Qatar and Turkmenistan are presented in this study. Change of R / P ratio has been associated with the political and economic events of the countries are being analyzed. The effect of political and economic changes on the ratio of natural gas R / P has been proposed.